Evidence for role of capillaries in regulation of skeletal muscle oxygen supply. (7th May 2021) - Ghonaim, Nour W.; Fraser, Graham M.; Goldman, Daniel; Milkovich, Stephanie; Yang, Jun; Ellis, Christopher G.
Abstract: How oxygen (O2 ) supply to capillaries is regulated to match the tissue's demand is unknown. Erythrocytes have been proposed as sensors in this regulatory mechanism since they release ATP, a vasodilator, in an oxygen saturation (SO2 )‐dependent manner. ATP causes hyperpolarization of endothelial cells resulting in conducted vasodilation to arterioles. Objective: We propose individual capillary units can regulate their own O2 supply by direct communication to upstream arterioles via electrically coupled endothelium. Methods: To test this hypothesis, we developed a transparent micro‐exchange device for localized O2 exchange with surface capillaries of intact tissue. The device was fabricated with an O2 permeable micro‐outlet 0.2 × 1.0 mm. Experiments were performed on rat extensor digitorum longus (EDL) muscle using dual wavelength video microscopy to measure capillary hemodynamics and erythrocyte SO2 . Responses to local O2 perturbations were measured with only capillaries positioned over the micro‐outlet. Results: Step changes in the gas mixture %O2 caused physiological changes in erythrocyte SO2, and appropriate changes in flow to offset the O2 challenge if at least 3–4 capillaries were stimulated. Conclusion: These results support our hypothesis that individual capillary units play a role in regulating their erythrocyte supply in response to a changing O2 environment.